Evaluation and Effectiveness of Dementia Staff Training Programs in General Hospital Settings: A Narrative Synthesis with Holton’s Three-Level Model Applied - Gkioka, Mara; Schneider, Julia; Kruse, Andreas; Tsolaki, Magda; Moraitou, Despina; Teichmann, Birgit (Journal of Alzheimer's disease, 2020)
Background: People with Dementia (PwD) are frequently admitted to hospital settings. The lack of proper dementia knowledge, poor communication skills, negative attitudes toward dementia, and lack of confidence affects the quality of care, thus develo
Gesehen am 18.01.2021